2020
DOI: 10.5114/ada.2019.83983
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Fatty liver Disease in Patients with Psoriasis - Therapeutic Implications

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver pathology in the western countries. Psoriatic patients are at higher risk of having NAFLD, and at higher risk of experiencing a more severe form of the disease with poorer outcomes. The components of the metabolic syndrome-obesity, lipid abnormalities, hypertension, and type 2 diabetes-significantly correlate with NAFLD progression. The inflammatory state present in psoriasis plays a significant role in development of NAFLD and the metabolic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
(94 reference statements)
0
9
0
2
Order By: Relevance
“…From a practical perspective, the psoriasis-NAFLD association not only has an impact on the severity of skin and liver lesions, but may also influence dermatologists’ decisions when selecting systemic treatment for psoriasis[ 62 , 79 ].…”
Section: Nafld and Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…From a practical perspective, the psoriasis-NAFLD association not only has an impact on the severity of skin and liver lesions, but may also influence dermatologists’ decisions when selecting systemic treatment for psoriasis[ 62 , 79 ].…”
Section: Nafld and Psoriasismentioning
confidence: 99%
“…Although some studies associate methotrexate liver toxicity with cumulative dose and treatment time, most find that the risk of liver damage is primarily related to the presence of risk conditions such as obesity, DM2, alcohol consumption, and NAFLD[ 80 , 81 ]. Cyclosporine and acitretin, a retinoid derived from vitamin A, are considered to be diabetogenic and to promote atherogenic dyslipemia and arterial hypertension[ 79 , 82 ].…”
Section: Nafld and Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Dotyczy około 2% populacji ogólnej [1]. Ostatnio wiele dowodów wskazuje, że PV nie jest chorobą ograniczoną wyłącznie do skóry, ale powinna być zaliczana do schorzeń metabolicznych ze względu na jej współistnienie z innymi zaburzeniami, takimi jak nadciśnienie tętnicze [2], niealkoholowe stłuszczenie wątroby [3], cukrzyca [4], otyłość [5] lub hipercholesterolemia [6]. Wskazuje się, że częstsze występowanie zaburzeń metabolicznych współistniejących z PV niż w grupie kontrolnej jest spowodowane ogólnoustrojowym stanem zapalnym, jednak nie udało się dotąd usystematyzować zależności między nimi.…”
Section: Wprowadzenieunclassified
“…Dermatology Review/Przegląd Dermatologiczny 2021/1 introduction Psoriasis vulgaris (PV) is one of the most common dermatoses and affects up to 2% of the general population [1]. Much recent evidence has shown that PV is not only limited to the skin, but should be considered as a metabolic disease due to the coexistence with, e.g., hypertension [2], non-alcoholic fatty liver disease [3], diabetes mellitus [4], obesity [5], or hypercholesterolaemia [6]. It has been suggested that increased prevalence of metabolic disturbances coexisting with PV is caused by systemic inflammation; however, no exact connections have been established yet.…”
mentioning
confidence: 99%